(untitled) (Revista Logos Ciencia & Tecnología, 2019)
This article describes a methodology that allows for the estimation of the coefficient of friction between the tire of a vehicle and the road surface, taking into account the emergency braking maneuvers applicable in the place where a traffic accident has occurred, as well as by the use of measuring equipment such as the Vericom accelerometer and, especially, the use of a smartphone, which turns out to be a reliable method for its accuracy in acquiring acceleration data. The methodology integrates protocols based on the standardization of procedures established by the SAE and the international standard ISO-21994.